Water-soluble SNS cationic palladium(II) complexes and their Suzuki–Miyaura cross-coupling reactions in aqueous medium - Fiebor, Alphonse; Tia, Richard; Makhubela, Banothile C. E.; Kinfe, Henok H. (Beilstein Journal of Organic Chemistry, 2018)
Unlike their SCS analogues, SNS pincer complexes are poorly studied for their use in coupling reactions. Accordingly, a series of water soluble cationic Pd(II) SNS pincer complexes have been successfully synthesised and investigated in detail for their catalytic activity in Suzuki–Miyaura coupling reactions. By using only 0.5 mol % loading of the complexes, the coupling of inactivated aryl bromides and activated aryl chlorides with various boronic acids in water was achieved in excellent yields and the catalysts were found to be reusable for three cycles without a significant loss of activity. The investigation of the mechanism of the reaction revealed that a Pd(II) to Pd(IV) route is the more likely pathway which was further supported by computational studies.
Keywords: cationic palladium(II) complexes; Pd(II)/Pd(IV) complexes; SNS pincer complexes; Suzuki–Miyaura